KAJIAN PENANAMAN KEDELAI DI BAWAH KELAPA SAWIT UMUR EMPAT TAHUN DI PTPN III KEBUN RAMBUTAN - Surya Wardhana; Lisa Mawarni; Asil Barus (Jurnal Agroekoteknologi, 2014)
To study the growth and yield of soybean under of oilpalm age four years at PTPN III KebunRambutan, a research has been done in February to May 2012. The design used was random plotdesign with two treatment. The first factor are varieties (Anjasmoro and Nanti) and the secondfactor are planting system (Square and Hexagonal planting system).The result showed that varietieshas significant effect of the plants length at 3, 4, 5, and 6 weeks after planting (WAP), amount ofleafs, age of flowering, weight of dry branches, production per plot, and amount of 100 seeds. Theplanting system has only influence of amount of 100 seeds. There was no interaction between thetwo treatments that was observed for all parameters.Keywords: soybean, planting system, and variety.